ANALISIS PERBANDINGAN KINERJA KEUANGAN PEMERINTAH PROPINSI SUMATERA BARAT DENGAN PROPINSI RIAU - Warnida Warnida (Universitas Negeri Padang, 2014)
This study aims to determine the financial performance of local governments in West Sumatera, Riau Province and to compare the financial performance of local governments in West Sumatra Province of Riau Province. This research was conducted at the local government of West Sumatra and Riau province using data derived from the financial statements of each of the provinces. The data used in this research is secondary data, Budgets and Budget Realization Report (LRA) provincial government West Sumatra and Riau in 2007 until 2009. The results of this study indicate that the degree of independence of the local government of West Sumatra province on average better than the local government of Riau Province. The effectiveness of local governments Riau province on average higher than the regional government of West Sumatra province. Keywords: government financial performance, level of independence, the level of effectiveness, Growth level